Study of the rheological behavior of simple and concentrated mango pulp (Mangifera indica L.) Variety Haden, in the thermal processing of pasteurization at different temperatures - Manayay Sánchez, Damián (2015)
Evaluate the rheological behavior: thixotropy, yield stress and flow characterization; also analyzed the effect of temperature and concentration on the rate of solid consistency and flow behavior, type viscometer using concentric cylinders through the methodology proposed by AOAC.The levels of soluble solids and heat treatment temperatures were considered in this study; between 16 to 18 ° Brixprocessed 80, 85, 90, 95 and 98 ° C and 28 ° Brix processed at 5, 15, 25, 35, 45, 55, 65 and 75 ° C. In simple pulp thixotropic behavior is not observed and has on the behavior of pseudoplastic fluid Herschel-Bulkley type; while concentrated to 28 ° Brix has thixotropic behavior and if appropriate adjustment of pseudoplastic Herschel-Bulkley fluid type. Rates consistency and flow behavior both simple pulp such as concentrated were placed respectively in the following limits: ± 2.07 0.76 ± 3.92 ≤ k ≤ 0.46 (Pa-sn); 0.27 ≤ n ≤ 0.35; 0.71 ± 1.64 ≤ 6° ≤60.11 ± 5.23 (Pa); 14.7 ≤ k ≤ ± 1.25 94.22 ± 4.84 (Pa-sn); 0.201 ± 0.007 < n < 0.352 ± 0.014. The threshold stress and consistency index decreased with the concentration of solids, while temperature has greater effect on the consistency index as the solids concentration increases.